Challenges and Strategies for Improving Training of Mid-Level Research Personnel in Nigeria - Echezona E. Ezeanolue; Theddeus Iheanacho; Dina V. Patel; Shatabdi Patel; Nadia Sam-Agudu; Michael Obiefune; Patrick Dakum; Prosper Okonkwo; Ayodotun Olutola; Hadiza Khamofu; Bolanle Oyeledun; Sani Aliyu; et al. (Ubiquity Press, 2019)
Background: Contextual research evidence is needed to reduce morbidity and mortality due to chronic but preventable diseases in low- and middle-income countries. Nigeria, Africa's most populous country, is particularly burdened by these diseases despite its academic and research infrastructure. A major impediment to developing robust evidence on sustainable disease prevention and treatment strategies is the lack of skilled research personnel. Objective: This study aimed to identify (1) training barriers for research assistants and coordinators and (2) potential strategies to counter these barriers using a Nominal Group Technique (NGT) exercise conducted at the 2017 conference of the Nigeria Implementation Science Alliance (NISA). Method: A one-hour NGT exercise was conducted with 26 groups of 2-9 persons each (N = 134) drawn from conference attendees. Group members were presented with questions related to the two objectives. Each member was asked to generate, list, discuss and vote on ideas that were eventually ranked by the group. Qualitative Thematic Analysis (QTA) was conducted for the collated responses. Findings: The QTA identified 166 training gaps and 147 potential solutions, out of which 104 were ranked. Themes that emerged for gaps included: 1) inadequate mentorship; 2) inadequate training/ lack of organized curriculum; 3) limited access to opportunities for training and employment; 4) lack of government funding; 5) lack of interest, motivation; and 6) lack of research culture. Themes for potential strategies to address the gaps were: 1) trainings/curriculum development; 2) research modules implemented in secondary and tertiary institutions; 3) creating a sustainable forum for research-related questions and answers; and 4) advocating for and accessing more government funding for research training. Conclusion: This study identified actionable strategies that reflect practical realities in implementation research in Nigeria, which can guide government agencies, policy makers, research organizations, and local foundations as they work together to increase research capacity in Nigeria.